THE PAIN OF A SPOT ON THE FOREHEAD - Mukhtorova Sevinch (Journals Park Publishing, 2024)
This article analyzes the story “Dog‘” by the writer Khaliyor Safarov. Some symbolic details in it are commented on, as well as a comparative analysis of image and dialogue motives with other works.
Keywords: the first sentence, the last sentence, comparative analysis, the motive of the conversation.